Pengembangan Bahan Ajar PowerPoint Interaktif Berbasis Teknologi Informasi dan Komunikasi (TIK) untuk Mata Kuliah Santripreneur - Suyyirah Suyyirah; Nurul Zainab; Miftahul Muttaqiin (Journal of Education and Teaching Learning, 2026)
This study aims to develop ICT-based teaching materials in the form of interactive learning media using Microsoft PowerPoint equipped with videos and discussion questions in the Santri Preneur course. The background is the minimal use of interactive media at IAI Al-Khairat Pamekasan, especially for Islamic boarding school students with limited access to digital devices and the internet. This study uses the R&D method with the ADDIE model. The media was validated by three experts with an average feasibility of 84.07% (very feasible), and implemented on 28 students of class PAI B Semester II. The results showed an increase in motivation, understanding, active participation, and learning outcomes with an average score of 84. All students responded positively to this media. Thus, this teaching material is considered feasible and effective as an innovative solution in contextual and interesting Islamic entrepreneurship learning in the Islamic boarding school environment. Based on the entire process, from needs analysis, expert validation, field implementation, and product refinement, it can be concluded that the development of this interactive PowerPoint teaching material was successful and highly suitable for use in learning. This medium can be an innovative alternative for developing Islamic entrepreneurship learning based on Islamic boarding schools that is enjoyable, applicable, and relevant to developments in educational technology.